Editorial - Capogna, Stefania; De Angelis, Maria Chiara (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This special issue, “Empowering Change. Navigating Twin Transitions and Enhancing Civic Engagement in Higher Education,” aims to promote interdisciplinary discussion on the link between environmental responsibility in higher education and active civic engagement, as well as on how higher education is evolving in response to digital, ecological, and demographic changes. It features the proceedings from the UP2YOU Workshop, "Navigating Twin Transitions and Enhancing Civic Engagement in Higher Education," held in conjunction with the 11th International Conference on Higher Education Advances (HEAd’25) in Valencia from June 17 to 20, 2025. The workshop aimed to showcase cutting-edge research and innovative ideas on utilizing digital tools and sustainable practices to create inclusive, future-oriented learning environments and to encourage civic engagement in higher education. This focus is particularly relevant in light of ongoing changes in the European Union labour market, which are shifting towards a service-based economy and are expected to drive growing demand for highly skilled workers by 2035. Rather than job polarization, a trend of job upgrading is emerging, with most job openings requiring high-level qualifications (Cedefop 2023).